A digital image encryption algorithm based on bit-planes and an improved logistic map. Issue 8 (April 2018) - Liu, Jingyi; Yang, Dingding; Zhou, Hongbo; Chen, Shiqiang
Abstract This paper presents a digital image encryption algorithm based on bit-planes and an improved logistic map. First, a chaotic sequence, which is generated by the improved logistic map, scrambles the pixels of the original image. Second, the scrambled image is split into a high 4-bit matrix and a low 4-bit matrix. The low 4-bit matrix is then introduced into the improved logistic model to generate a chaotic sequence that is highly correlated with the image as the key, and the key is used for position scrambling and the XOR operation of the high 4-bit matrix. Finally, the two matrices are combined into an 8-bit image matrix to obtain the ciphertext image. The algorithm has a significant one-time pad characteristic. MATLAB simulation experiments are conducted to analyze the security of image encryption in terms of the histogram, plaintext sensitivity, information entropy, and adjacent pixels correlation index. Experimental results show that the number of pixel changes ratio (NPCR) is greater than 90% and the information entropy of the ciphertext image reaches 7.99, demonstrating that the algorithm offers good encryption.